POLITICAL CONNECTION, FAMILY OWNERSHIP, AND EARNINGS MANAGEMENT IN MANUFACTURING COMPANIES IN INDONESIA - Savitri, Enni (Universitas Brawijaya, Indonesia, 2021)
Political connections have an essential role in the earnings management strategy. Political connections can influence earnings management practices. The research aimed to analyze the effect of politics and family ownership on earnings management practices. The sample is 92 manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2019. Methods of data using a purposive sampling method. Multiple linear regression is an analytical tool used to test the hypothesis. The results show that political connections influence profits. The company pays more attention to the company's reputation and maintains the privileges of the political relationship that has existed between the company and the government. Family ownership affects earnings management. Family ownership has control rights that can be used to influence management in company profits. The novelty of this research is that political connections can influence earnings management.